Controle biológico e caracterização fisiológica de Sclerotinia sclerotiorum provenientes de plantas de soja cv. ‘SoyTech 797 Ipro’ - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
The fungus Sclerotinia sclerotiorum that causes the commonly known disease of white mold is a phytopathogen that attacks crops of great importance in agriculture and the fight against its symptoms has been innovative through biocontrol, and the treatment with Trichodermas is a timely alternative for environmental sustainability. The objective of this work was to perform the physiological characterization of Sclerotinia sclerotiorum isolates and to evaluate Trichoderma spp. strains in the germination and vigor of soybean seeds, as well as in the biological control of Sclerotinia sclerotiorum inoculated in the seeds. The strains evaluated were: T. harzianum CCT 7589, Mix (T. harzianum + T. asperellum + T. koningiopsis) and T. asperellum URM 5911. After tests evaluating the mycelial growth of S. sclerotiorum, isolates A43-01 and A-43-05 were selected for seed testing. The tests used healthy and contaminated seeds in both treated with Trichoderma spp. strains. After treatment, the seeds were incubated in BOD at 25°C and photoperiod of 12 hours and evaluated at 8 days after sowing (DAS). The number of dead seeds, normal seedlings, abnormal seedlings, according to the Rules for Seed Analysis, root length and shoot of each seedling considered normal were evaluated. The experiments were conducted in a completely randomized design (DIC), with four replicates for each strain of Trichoderma. The selected isolates stood out in relation to the others in terms of surface colonization capacity. This characteristic allowed the selection of isolates with high virulence for the assay with soybean seeds. The commercial strains evaluated did not cause an adverse effect on seed germination when compared to the control, proving to be nontoxic to the seeds. The treatment composed of a mixture of three species of Trichoderma Mix (T.h + T.a + T.k) provided higher MFT and MSPA, suggesting greater allocation of biomass for the shoot.
Keywords: Glycine max; controle biológico; micologia; Glycine max, biological control; biological control; mycology; CIENCIAS AGRARIAS::AGRONOMIA